Glycoconjugate Binding of Gastric and Enterohepatic Helicobacter spp. - Hynes, Sean O. (American Society for Microbiology, 2003)
Helicobacter pylori is able to utilize several lectin-like, protein-carbohydrate interactions for binding to mucins, cell surfaces, and extracellular matrix proteins. As determined by hemagglutination assays and binding of radiolabeled bacteria to glycosphingolipids on thin-layer chromatograms, strains of gastric helicobacters and enterohepatic helicobacters, including Helicobacter canis, Helicobacter hepaticus, and Helicobacter bilis, also demonstrated evidence for the presence of lectin-hemagglutinin adhesins. In addition, in H. hepaticus and H. bilis, binding may be sialic acid dependent. The presence or absence and differences in the levels of activity of lectin adhesins may reflect the species' ecological niche.